Court companion on gender based violence cases. - Abdul Aziz, Zarizana (Asian Development Bank, 2021)
Affecting one in three women in the world, gender based violence is pervasive but invisible. Social taboos, patriarchal norms, and gender unsensitized legal frameworks prevent victims from attaining justice. This publication is particularly useful for judges, prosecutors, and other justice sector stakeholders. It is also for anyone interested in pursuing justice, holding perpetrators accountable, and providing effective redress and reparation to victims of gender based violence.